Optimal unconventional monetary policy in the face of shadow banking - Philipp Kirchner; Benjamin Schwanebeck (Philipps-University Marburg, School of Business and Economics, 2017)
Using a DSGE framework, we discuss the optimal design of monetary policy for an economy where both retail banks and shadow banks serve as financial intermediaries. We get the following results. During crises times, a standard Taylor rule fails to reach sufficient stimulus. Direct asset purchases prove to be the most effective unconventional tool. When maximizing welfare, central banks should shy away from interventions in the funding process between retail and shadow banks. Liquidity facilities are the welfare-maximizing unconventional policy tool. The effectiveness of unconventional measures increases in the size of the shadow banking sector. However, the optimal response to shocks is sensitive to the resource costs of the implementation which may differ across central banks. Hence, optimal unconventional monetary policy is country-specific.
Keywords: E44; E52; E58; 330; financial intermediation; shadow banking; financial frictions; unconventional policy; optimal policy